Pengelolaan Data Bank Sampah Damai Bestari Kelurahan Sidomulyo Timur Kecamatan Marpoyan Damai Pekanbaru - Yustina Yustina; Hendra Taufik; Nelvia Nelvia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The BESTARI Peaceful Waste Bank (Clean, Firm and Beautiful) in the East Sidomulyo sub-district, Marpoyan Damai District, Pekanbaru has received less response from local residents, allegedly related to data processing problems. This P2M activity aims to provide training to design a data processing system, can be used as information, evaluate performance and analyze progress and obstacles. The benefits of activities are more efficient in making the desired transaction reports. Methods of application: 1.Identification of Data Management and Processing Problems, 2.Training of organic waste processing skills online, 3. Recap and analyze the BESTARI peaceful waste bank data, 4. Training of offline waste bank data processing skills. Reached the target shows 90% of waste bank officers are skilled at processing and displaying more informative data in the form of tables and graphs. Increased interest in customer participation in responding to discussions. In conclusion, this data processing has achieved its target, namely increasing knowledge, skills of participants in managing data, viewing and displaying customer data more informatively, facilitating transactions, and minimal data errors and increasing the security and trust of BESTARI Peace Bank customers.